Thirty-Day Perioperative Complications, Prolonged Length of Stay, and Readmission Following Elective Posterior Lumbar Fusion Associated With Poor Nutritional Status. Issue 4 (June 2019) - Phan, Kevin; Ranson, William; White, Samuel J. W.; Cheung, Zoe B.; Kim, Jun; Shin, John I.; Ukogu, Chierika; Lee, Nathan J.; Kothari, Parth; Cho, Samuel K.
Study Design: Retrospective study. Objective: To determine the rates of early postoperative mortality and morbidity in adults with hypoalbuminemia undergoing elective posterior lumbar fusion (PLF). Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) was examined from 2005 to 2012. Current Procedural Terminology (CPT) codes were used to query the database for adults (≥18 years) who underwent PLF and/or posterior/transforaminal lumbar interbody fusion (PLIF/TLIF). Patients were divided into those with normal albumin concentration (≥3.5g/dL) and those with hypoalbuminemia (<3.5 g/dL). Both univariate and multivariate analyses were performed. Results: A total of 2410 patients were included, of whom 2251 (93.4%) were normoalbuminemic and 159 (6.6%) were hypoalbuminemic. Patients with preoperative serum albumin levels <3.5 g/dL were older with a higher American Society of Anesthesiologists (ASA) score, and more comorbidities, including anemia, diabetes, dependent functional status, and preoperative history of chronic steroid therapy. Hypoalbuminemic patients had higher rates of any 30-day perioperative complication ( P < .001), unplanned readmission ( P = .019), and prolonged length of stay (LOS) >5 days ( P < .001). However, hypoalbuminemia was not significantly associated with any specific perioperative complication. On multivariate analysis, preoperative hypoalbuminemia was found to be an independent predictor of prolonged LOS (OR 2.4, 95% CI 1.7-3.5; P < .001) and unplanned readmission (OR 2.7, 95% CI 1.1-6.3; P = .023). Conclusion: Hypoalbuminemia was found to be an important predictor of patient outcomes in this population. This study suggests that clinicians should consider nutritional screening and optimization as part of the preoperative risk assessment algorithm. Level of Evidence: III